GENETIC DETERMINANTS OF ANTIBIOTIC RESISTANCE AND VIRULENCE IN Staphylococcus aureus ISOLATES FROM HOSPITAL SURFACES IN HIGH-RISK AREAS OF LOJA, ECUADOR - LIMA- QUIZHPE, Cristina; ANDRADE- TACURI , Carlos; ORTIZ-TEJEDOR, Jonnathan; ORELLANA-BRAVO , Paola; TOLEDO-ANDRADE , Karla (African Journal of Infectious Diseases (AJID), 2025)
Background: Staphylococcus aureus is a microorganism associated with nosocomial infections, characterized by its high pathogenicity and antibiotic resistance, posing a critical risk in hospital environments. This study aimed to determine its presence, antibiotic susceptibility, and the detection of virulence, adhesion, and regulatory genes on hospital surfaces using phenotypic and molecular methods. Materials and Methods: A total of 200 surface samples were collected from a secondary-level hospital, including clinical wards, ICU, and emergency areas. S. aureus was isolated using phenotypic techniques (mannitol, coagulase, DNase) and genotypic methods (detection of nucA and femB). Antimicrobial susceptibility was evaluated using the Kirby-Bauer method. Polymerase Chain Reaction (PCR) was employed to identify resistance and virulence genes. Results: S. aureus was detected in 7.5% of the samples analyzed, with higher prevalence in Clinic I and Emergency areas. The most contaminated surfaces included door handles, tables, and keyboards, identified as critical transmission points. Among the isolated strains, 66.6% were resistant to penicillin, while 100% were sensitive to methicillin and vancomycin. Virulence genes (tst, sea) were present in 26.6% and 13.3% of the strains, respectively. Regarding regulatory genes, agrI (73.3%) was the most common, followed by agrIII. For adhesion factors, icaD and icaC were the most frequently detected genes. Conclusion: These findings highlight the pathogenic potential of S. aureus and its ability to persist on inert surfaces, representing a significant risk for infection transmission.